IMPLEMENTASI PELAPORAN KEUANGAN BERBASIS AKRUAL PADA PERGURUAN TINGGI NEGERI BADAN HUKUM: ANALISIS DESKRIPTIF KUALITATIF - Rosalia Rosalia; Warsito Kawedar (Diponegoro Journal of Accounting, 2017)
This study aims to describe how implementing accrual based in the financial report of the Perguruan Tinggi Negeri Badan Hukum (PTN BH). This study focused on the PTN BH university to get data which related with beginning preparation on implementing financial report based accrual. The location of this study is Diponegoro University (Undip). This study using qualitative descriptive approach with interview and observation methods. Interviews were conducted to Undip’s accounting staff. Observation method were done by attended on accounting staff’s meeting. Data from interview and observation analyzed using Miles and Huberman model and categorized as major determinants on implementing accrual based PTN BH university financial report. The results show that determinants which affect on implementing accrual based in financial report’s PTN BH university are: Accounting system, IT based system, competent human resources, commitment from leader, resistance, environment, and internal policy. Every determinant related each other. Accounting system based on IT used by competent human resources which needs commitment from leader to avoid the resistance. Majelis wali amanat consist of environment element have to keeping on track of university financial reporting. Every rules which relate with implementing accrual based in PTN BH university financial report will be settled as policy in many degrees.